A study of alternative capital structure theories in the Malayasian context - Ismail, Faizah. (2006)
This thesis examines the relevance of the western capital structure theories – the static trade-off theory and the pecking order model - in providing plausible explanation of Malaysian corporate financing decisions from 1991 to 2000. To achieve this objective, the empirical analyses have been divided into three parts: (1) the first analysis examines the determinants of capital structure based on the Malaysian proposed factors and the theory-related attributes. (2) The second part tests the static trade-off theory (via target-adjustment model) and the pecking order model, separately and jointly, in seeking the applicability of the theory descriptions. (3) The final analysis evaluates the performance of the developed models when judged on explanatory power. The empirical analyses of the thesis adapt Shyam-Sunder and Myers' (1999) model specifications and the subsequent criticisms by Chirinko and Singha (2000), with several revisions and adjustments to fit our enquiry.